Calcium pyrophosphate dihydrate (CPPD) deposition in ochronotic arthropathy. Issue 8 (August 1983) - McClure, J; Smith, P S; Gramp, A A
Abstract : The post-mortem examination of an unsuspected case of alkaptonuria revealed extensive ochronosis. Histological examination of undecalcified sections of tracheal, costal, femoral and patellar cartilage revealed, in addition to ochronotic pigment, extensive calcium pyrophosphate dihydrate (CPPD) deposition. Similar deposits were present in intervertebral discs and were related to ossification of the discs resulting in partial or complete ankylosis. The calcific deposits were present around chondrocytes in the articular cartilage and this may be an important factor in the initiation of the osteoarthrotic process which characterises ochronotic arthropathy as it affects large diarthrodial joints.